Estudos sobre a síntese de derivados quinolínicos promovida pelo pentacloreto de nióbio para utilização como corantes sensibilizadores em dispositivos fotoeletroquímicos de gratzel - Santos, Giovanny Carvalho dos [UNESP] (2015)
The development of new synthetic strategies for an efficient production of organic compounds is very importante. Among these compounds, quinolites show a variety of applications in various areas and ares present in many natural products and drugs. Thus, in this work we have studied the synthesis of such derivatives by using niobium pentachloride as promoter in multicomponent reactions carried out between p-nitroaniline, phenylacetylene and benzaldehyde derivatives, at room temperature, which were obtained good yields (54-98%) in a good reaction time. We also analyze the effectiveness of niobium pentachloride compared to other catalysts, which showed that the NbCl5 is a good promoter in this reaction. We them carried the reduction of the nitro group present in the synthesized compounds were submitted to analysis of structural, photochemistry and photophysics characterization, aminoquinolines derivatives showed the highest potential for application as sensitizing dyes in photoelectrochemical devices of Gratzel and for use in order organic electronic devices